Brazil’s New Gas Law: Analysis, Implications, and Remuneration of Gas Processing Plants with Non-Discriminatory Access to Customers - Junior, Samuel Mathias do Amaral; Padilha, Janine Carvalho; Arrieche, Leonardo (International Journal of Energy Economics and Policy, 2024)
Brazil will increasingly rely on the availability of natural gas as new discoveries in the Pre-Salt portion are explored. Currently, a substantial amount of the gas produced associated with oil is reinjected (60,84 million m³/day in 2021, according to the Ministry of Mines and Energy), with the lack of structure being one of the factors for this non-energy purpose. The New Gas Law proposes to fill this gap by stimulating investments in infrastructure. In this sense, market opening has the potential to promote the rupture of natural monopolies by providing access to infrastructure, including Natural Gas Processing Plants (NGPP). This units, in addition to conditioning the gas for sale, allow the recovery of higher molecular weight fractions, or (Natural Gas Liquid). However, the instructions for this access required by the government are insufficient for issues related to the NGL recovery efficiency of these units, as well the method of remuneration arising from the NGL production capacity. It is proposed in this paper to include a processing tariff, based on static simulation of available technological routes. Comparison of energy spent and NGL recovery efficiency will allow to formulate the gas price, unfolding from the price of the molecule.